PENGARUH SITUATION-BASED LEARNING TERHADAP KEMAMPUAN MATHEMATICAL PROBLEM POSING DAN SELF-EFFICACY SISWA - Tikamala, Tikamala; Isrokatun, Isrokatun; Maulana, Maulana (Jurnal Pena Ilmiah, 2019)
This research is conducted on the basis of the importance of students self-efficacy and mathematical problem posing (MPP) abilities as a main ability to improve their mathematical abilities. Situation-Based Learning (SBL) is one of the correct choices to improve self-efficacy and MPP ability. The research method used was a quasi experiment with nonequivalent control group design. The population of the study is all fourth grades students in sub-district Darma, Kuningan District. Meanwhile, the samples of the research is in SDN 1 Darma as the experimental class and SDN 2 Bakom as the control class. The research instruments are used MPP ability test questions, attitude scale self-efficacy questionnaire, student response questionnaire, teacher performance observation sheet and student activities, and field notes. Based on the learning outcomes for four meetings, it shows that: 1) the two classes have a positive influence on MPP's abilities and there are significant differences, SBL is better than conventional learning; 2) SBL has a better influence on self-efficacy than conventional learning; 3) there is no relationship between self-efficacy and MPP ability; and 4) students gave a very positive response to SBL learning.Keywords: Situation-Based Learning (SBL), Mathematical Problem Posing (MPP) Ability, Self-Efficacy.